Student Entrepreneurship and Innovation Competition (2022)
Consuming food with high nutritional value, reducing the negative impacts that indiscriminate cultivation causes in nature, and the low competitiveness of farming families against agricultural industries, are issues that Colombian society face nowadays. VEGY is an App that amid to act as a direct bridge between farming families and buyers who want to obtain their crops or rent a piece of land to harvest. The App also offers complete information about the agricultural product; location, planting day, harvesting and storage. We categorize in the service sector, particularly the sector of buying and selling agricultural food; vegetables, fruits, tubers, etc. Finally, the profile of our customers ranges between the ages of 18 and 45 years, who may be owners of medium and small businesses belonging to the food sector; food restaurants, community stores, farmers markets, etc., not forgetting family households passionate about environmental, technological and social issues.